2003
DOI: 10.1083/jcb.200306033
|View full text |Cite
|
Sign up to set email alerts
|

Multiple EphB receptor tyrosine kinases shape dendritic spines in the hippocampus

Abstract: Here, using a genetic approach, we dissect the roles of EphB receptor tyrosine kinases in dendritic spine development. Analysis of EphB1, EphB2, and EphB3 double and triple mutant mice lacking these receptors in different combinations indicates that all three, although to varying degrees, are involved in dendritic spine morphogenesis and synapse formation in the hippocampus. Hippocampal neurons lacking EphB expression fail to form dendritic spines in vitro and they develop abnormal spines in vivo. Defective sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
248
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 266 publications
(264 citation statements)
references
References 35 publications
12
248
3
Order By: Relevance
“…The ability to modulate Rho-GTPase activity in neurons is critical during development to regulate neurite outgrowth, growth cone collapse, and axon guidance [87], and, more recently, as regulators of excitatory synapse formation, function, and plasticity in the central nervous system [88]. Indeed, several EphR and ligands localize with postsynaptic density marker PSD95 at excitatory synapses in hippocampal neurons, including EphA4, EphB1, EphB2, and EphB3 [90][91][92][93][94][95]. To date, at least 2 EphRs have been linked to AD.…”
Section: Erythropoietin-producing Hepatocellular Receptor Signalingmentioning
confidence: 99%
“…The ability to modulate Rho-GTPase activity in neurons is critical during development to regulate neurite outgrowth, growth cone collapse, and axon guidance [87], and, more recently, as regulators of excitatory synapse formation, function, and plasticity in the central nervous system [88]. Indeed, several EphR and ligands localize with postsynaptic density marker PSD95 at excitatory synapses in hippocampal neurons, including EphA4, EphB1, EphB2, and EphB3 [90][91][92][93][94][95]. To date, at least 2 EphRs have been linked to AD.…”
Section: Erythropoietin-producing Hepatocellular Receptor Signalingmentioning
confidence: 99%
“…Changes in hippocampal spine density and dimensions occur in several mental disorders, including depression, schizophrenia and addiction. Another study has shown that EphB1, EphB2, and EphB3 are involved all three, although to varying degrees, in dendritic spine morphogenesis and synapse formation in the hippocampus (Henkemeyer et al, 2003). All these candidates are up regulated in that region in all protocols of drug administration…”
Section: Eph Receptors and Related Ephrin Ligands Display Significantmentioning
confidence: 99%
“…Immunolabeling of Eph receptors confirmed their localization in dendritic shafts, filopodial protrusions, and spine heads [45,57,68]. Henkemeyer and colleagues observed that in EphB1/B2-and EphB1/B2/B3-deficient mice, dendritic spines failed to develop [34]. F-actin rich spines were replaced by thin filopodia-shaped protrusions that lacked clustered F-actin.…”
Section: Eph Receptors and Spine Morphogenesismentioning
confidence: 91%